Profitability Conventional Banking : Are influencing Inflation, Capital Resilience, Efficiency in Fund Gathering and Allocation? - Novi Darmayanti; Ana Fitriyatul Bilgies; Sevira Lupita Anjani; Martin Yehezkiel Sianipar; Yerisma Welly (Owner : Riset dan Jurnal Akuntansi, 2023)
This research aims to examine and analyze the influence of inflation, Capital Adequacy Ratio, Loan to Deposit Ratio, and mobile banking on the profitability of conventional commercial banks (an empirical study of conventional commercial banks listed on the Indonesia Stock Exchange from 2018 to 2022). The research design has a causal associative nature with a quantitative approach. The population in this study consist of conventional commercial banks listed on the Indonesia Stock Exchange that implemented mobile banking technology for five consecutive years during the period 2018-2022. The sampling technique used is purposive sampling, resulting in 6 samples out of 30 conventional commercial banks. Data analysis is conducted through descriptive analysis, inner model analysis, outer model analysis, and hypothesis testing using the SmartPLS v.3.2.9 software. The research findings indicate that the variables of inflation, Capital Adequacy Ratio, and Loan to Deposit Ratio have a positive and significant impact on the profitability on conventional commercial banks. However, the mobile banking variable does not have a significant impact on the profitability of conventional commercial banks